Penerapan Model Team Games Tournament (TGT) dalam Pembelajaran PKn di SMPN 1 Padang - Eliza, Gusma (Jurnal Demokrasi, 2011)
The objectives of this study were to increase student motivation and activeness in learning process of civic education through the use of Team Games Tournament (TGT) model and to drill thinking skills as well as self-confidence of the students. This study was conducted through a Classroom Action Research at E VII international class of SMPN 1 Padang. This classroom action research consisted of two cycles. The finding of this study indicated that TGT model was very significant to increase motivation and and activeness of students in learning process of civic education. It is suggested that this model of TGT could be applied in other classes and subject areas of study with the adjustment of the model with the subject matters of the classes. Â  Kata Kunci: Model TGT, Aktifitas Belajar, Pembelajaran PKn Pendidikan Kewarganegaraan,